9(-10+x)-5(2x+9)=4-x+11

Simple and best practice solution for 9(-10+x)-5(2x+9)=4-x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(-10+x)-5(2x+9)=4-x+11 equation:


Simplifying
9(-10 + x) + -5(2x + 9) = 4 + -1x + 11
(-10 * 9 + x * 9) + -5(2x + 9) = 4 + -1x + 11
(-90 + 9x) + -5(2x + 9) = 4 + -1x + 11

Reorder the terms:
-90 + 9x + -5(9 + 2x) = 4 + -1x + 11
-90 + 9x + (9 * -5 + 2x * -5) = 4 + -1x + 11
-90 + 9x + (-45 + -10x) = 4 + -1x + 11

Reorder the terms:
-90 + -45 + 9x + -10x = 4 + -1x + 11

Combine like terms: -90 + -45 = -135
-135 + 9x + -10x = 4 + -1x + 11

Combine like terms: 9x + -10x = -1x
-135 + -1x = 4 + -1x + 11

Reorder the terms:
-135 + -1x = 4 + 11 + -1x

Combine like terms: 4 + 11 = 15
-135 + -1x = 15 + -1x

Add 'x' to each side of the equation.
-135 + -1x + x = 15 + -1x + x

Combine like terms: -1x + x = 0
-135 + 0 = 15 + -1x + x
-135 = 15 + -1x + x

Combine like terms: -1x + x = 0
-135 = 15 + 0
-135 = 15

Solving
-135 = 15

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5x-50=15 | | -19y=2x+.05 | | 6x+2+2-3x=-4(6x-3)+3(-x-3) | | 6a+17=-1 | | -2(2x+5)=-2+4x | | .27=x*75 | | x+.07x=15877 | | (4x+8y^2)(x-y^2)=0 | | 5h+21=11 | | W-19=6+9w | | 4(-4x+6)=-6(1+2x)-x | | X+x*4-144=0 | | -p+5=25-6p | | -5(k-3)=-90 | | 3g+17=5 | | .75*80= | | 2-x=-5(x-2) | | 4f-3=13 | | -3+2x=-(4-x) | | 2sin(x)-3=-2 | | 5d-7=23 | | 7=2x^2+6x+7 | | -3(5+3x)=4x-2 | | B+8=1 | | -.7x+26.9=-x+29 | | 10-x+6x=-x-4x | | -22=-6+k | | 24+8x=40 | | X^2+kx-k+8=0 | | -22=-6+6 | | 3(x+6)=2(3x+15) | | -7x+26.9=-x+29 |

Equations solver categories